Hemipenile prolapse and hemipenectomy in a leopard gecko (Eublepharis macularius) - Lescano, J. (2016)
Copulatory organ prolapse is a condition more frequently observed in chelonians and ophidians than in lizards. Most common causes are infections, forced separation during mating and inflammation associated to the use of probes for sex determination. Moreover, many other predisposing factors are described (hypocalcaemia, urolithiasis, etc.), but etiological diagnosis is rarely achieved. A four years old leopard gecko (Eublepharis macularius) was received presenting unilateral hemipenile prolapse. Medical therapy was performed using 50 % dextrose baths and prednisone (2 mg/kg) during 24 hours, but it was unsuccessful. Due to the fact that the prolapsed hemipenis showed signs of necrosis, surgical resection was performed. The patient was anesthetized using the combination ketamine (5 mg/kg), dexmedetomidine (0.1 mg/kg), and midazolam (1 mg/kg); also, lidocaine (4 mg/ kg) was administered for local block, whereas atipamezole (0.5 mg/kg) was used for antagonizing dexmedetomidine. The used anesthetic protocol allowed an adequate surgical management. Hemipenectomy solved the problem without any observed complication.